Regulating Cryptocurrencies in the International Insolvency Law - Sandberg, Victoria (My University, 2020)
In the last few years, the world has witnessed a fast expansion of bitcoin and other cryptocurrencies. From being mostly associated with criminal activity in their earliest years, cryptocurrencies have now taken a step into the legal business markets. The increased use of cryptocurrencies in business and commercial transactions entails that their appearance in the insolvency proceedings can be expected in a foreseeable future. However, the fast development of cryptocurrencies means that the current regulatory frameworks around the world have not kept up with the changes, which is especially noticeable in international situations. The continuous growth of cryptocurrencies and their value indicate that they will become very interesting for insolvency practitioners in the future, but the lack of regulation and case law within this field raises the question of how they will and should be treated. While cryptocurrencies continue to find their place in modern society, whether and to what extent they should be regulated in the international insolvency law is a vastly approaching issue. This thesis discusses the possibility of regulating cryptocurrencies on the international level of the insolvency law by examining firstly, the different risks and issues that the cryptocurrencies will give rise to in the insolvency law and insolvency proceedings with a special focus on jurisdiction, secondly, the current regulatory frameworks and principles on international and European Union level and lastly, the possibilities of regulation through both soft law and hard law in order to create a way to approach these problems. The possibility of regulation will be discussed in a multidisciplinary light, with the principles of international financial law as well as the nature of blockchain-based technology taken into consideration. The aim of the thesis is not to come up with a specific course of action, but rather to enlighten the most prominent pros and cons of different possibilities. The potential ways of regulation brought up in the thesis are the use of blockchain technology itself, amendment of existing legal frameworks, the use of regulatory sandboxes and a new legal framework.

Viime vuosina maailma on todistanut bitcoinin ja muiden kryptovaluuttojen nopean laajentumisen. Kryptovaluutat yhdistettiin alkuaikoina usein rikollisiin tarkoituksiin, mutta lähivuosina kryptovaluutat ovat siirtyneet myös laillisille liiketoimintamarkkinoille. Kryptovaluuttojen käytön lisääntyminen markkinoilla ja kaupallisissa liiketoimissa tarkoittaa, että niiden ilmeneminen maksukyvyttömyysmenettelyissä on lähitulevaisuudessa odotettavaa. Kryptovaluuttojen nopea kehitys tarkoittaa kuitenkin sitä, että nykyinen sääntely ei ole pysynyt muutosten mukana, mikä on erityisesti havaittavissa kansainvälisissä tapauksissa. Kryptovaluuttojen jatkuva kasvu sekä niiden arvo markkinoilla osoittaa, että ne tulevat tulevaisuudessa olemaan mielenkiintoinen osa insolvenssioikeuden asiantuntijoiden työtehtäviä. Mutta sääntelyn sekä oikeuskäytännön puute herättää kuitenkin kysymyksiä siitä, miten kryptovaluuttojen kanssa tulisi toimia. Kryptovaluutat etsivät jatkuvasti paikkaansa nykyaikaisessa yhteiskunnassa, mutta kysymys siitä, miten niitä pitäisi säännellä kansainvälisessä insolvenssioikeudessa ja missä laajudessa, on nopeasti lähestyvä haaste. Tässä opinnäytetyössä keskustellaan mahdollisuudesta säännellä kryptovaluuttoja insolvenssioikeuden kansainvälisellä tasolla tutkimalla ensinnäkin erilaisia riskejä ja ongelmia, joita kryptovaluutat aiheuttavat insolvenssioikeudessa ja maksukyvyttömyysmenettelyissä kiinnittäen erityistä huomiota lainkäyttövaltaan. Tämän lisäksi tutkitaan insolvenssioikeuden nykyisiä laillisia kehyksiä ja periaatteita kansainvälisellä ja Euroopan Unionin tasolla. Viimeiseksi pohditaan sääntelymahdollisuuksia sekä sitovalla että ei-sitovalla sääntelyllä luomalla tapaa lähestyä niitä haasteita, jotka kryptovaluutat aiheuttavat. Sääntelymahdollisuudesta keskustellaan monialaisessa valossa, ottaen huomioon kansainvälisen finanssioikeuden periaatteet sekä blockchain-teknologian luonteen. Opinnäytetyön tarkoituksena ei ole keksiä tiettyä toimintatapaa, vaan valaista eri mahdollisuuksien hyötyjä ja haittoja. Opinnäytetyössä esiin tuodut mahdolliset sääntelytavat ovat blockchain-teknologian käyttäminen, olemassa olevien laillisten kehysten muuttaminen, sääntelyn hiekkalaatikoiden käyttäminen sekä uusi oikeudellinen kehys.
Keywords: International insolvency law, Cryptocurrency, Blockchain, Technology, Jurisdiction, Regulation